2015
DOI: 10.3923/ajpsaj.2015.233.241
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Poultry Farmers’ Participation in Livestock Insurance in Southwest Nigeria

Abstract: Poultry birds are primarily exposed to the risk of death caused by various types of diseases. In many cases, epidemic diseases can cause catastrophic losses from deaths of an entire stock of livestock. In the light of this, this study was designed to examine the determinants of poultry farmers' participation in livestock insurance in southwest Nigeria. Primary data were obtained with the aid of structured questionnaire from a cross section survey of 403 poultry farmers drawn through multi-stage sampling proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 6 publications
7
16
1
Order By: Relevance
“…Access to extension services and being a member of a farmer-based organisation also lead to differences in willingness to participate in the WII scheme at p o0.1 and p o0.05, respectively. This is consistent with previous studies, where a positive relationship was reported between either access to extension services or membership of farmer organisations and participation in agricultural insurance schemes as extension officers briefed farmers regarding the benefits of insurance cover or farmers could discuss the benefits of insurance within the farmer group (Akintunde, 2015;Ali, 2013;Ellis, 2016;Wairimu et al, 2016).…”
Section: Initial Offersupporting
confidence: 90%
“…Access to extension services and being a member of a farmer-based organisation also lead to differences in willingness to participate in the WII scheme at p o0.1 and p o0.05, respectively. This is consistent with previous studies, where a positive relationship was reported between either access to extension services or membership of farmer organisations and participation in agricultural insurance schemes as extension officers briefed farmers regarding the benefits of insurance cover or farmers could discuss the benefits of insurance within the farmer group (Akintunde, 2015;Ali, 2013;Ellis, 2016;Wairimu et al, 2016).…”
Section: Initial Offersupporting
confidence: 90%
“…Average farm size for most youths was two hectares. This is in agreement with Akintude (2016) who asserted that few youths are interested in farming. The average of house hold size was five persons.…”
Section: Resultssupporting
confidence: 91%
“…This implies that increasing stock size increases amount intensity by GH¢ 0.061 (US$ 0.010). Akintunde (2015) observed a similar effect. FBO membership had a positive and significant influence on aquaculture insurance participation and amount intensity.…”
Section: Perceptions Of Aquaculture Insurance Prospects In Ghanamentioning
confidence: 55%